Answer:
see explanation
Step-by-step explanation:
Given the 2 equations
2x - 3y = - 2 → (1)
4x + y = 24 → (2)
Multiplying (1) by - 2 and adding to (2) gives
- 4x + 6y = 4 → (3)
Add (2) and (3) term by term
(4x - 4x) + (y + 6y) = (24 + 4), that is
7y = 28 ( divide both sides by 7 )
y = 4
Substitute y = 4 into either of the 2 equations
Substituting y = 4 into (2)
4x + 4 = 24 ( subtract 4 from both sides )
4x = 20 ( divide both sides by 4 )
x = 5
Thus the answers x = 5 and y = 4 are the same as her first method